Effectiveness of intravenous bisphosphonate in treatment of giant cell tumor: A case report and review of the literature - Olarn Arpornchayanon (2018)
Giant cell tumor is a benign locally aggressive tumor. The standard treatment is en bloc resection followed by major reconstructive surgery, or extended curettage conjunction with bone grafting or the use of bone cement implantations. Surgical treatment of giant cell tumor at the sacrum is associated with high morbidity, and local recurrence. The authors present a case of giant cell tumor at the sacrum treated with intravenous 4 mg zoledronate every 4 weeks for seven courses followed with curettage and cement implantation. At two years follow-up, the patient had no pain, no neurological deficit, and no local recurrence. The patient's gait was normal. From the present study, the authors demonstrate the effectiveness of zoledronate for treatment of giant cell tumor at the sacrum. It can reduce the morbidity from major surgery.